Pengaruh Kompetensi Pedagogik dan Gaya Mengajar terhadap Hasil Belajar PAI Siswa SMP IT Khairul Imam - Sarifah Hanum Gea; Sapri Sapri; Makmur Syukri (Ideguru: Jurnal Karya Ilmiah Guru, 2024)
This exploration mirrors a pledge to additionally foster understudy learning accomplishments by considering instructive capacity elements and instructors' showing styles on understudy PAI learning results at Khairul Imam IT Center School, Medan City. The point of this examination is to figure out what instructor educational capability means for understudies' PAI learning results at Khairul Imam IT Center School, Medan City. The assessment procedure utilized is a quantitative strategy with correlational investigation methods. The data assortment system for the instructive capacity variable is brought out through non-test assessments of public sentiment. The test instrument for evaluating teachers' instructive abilities and the way of showing them is a study. The consequences of the assessment show that there is a positive and huge impact between instructive abilities and dominance results. In this manner, the higher and more certain the scholastic capacities made by teachers, the higher and more certain the expansion in understudy PAI learning results at Khairul Imam IT Center School, Medan City. The finish of this examination is that there is a significant impact between showing capacity and the instructor's exhibition style on understudy PAI learning results at the Khairul Imam IT Center School, Medan City.